Ranibizumab and Bevacizumab for Treatment of Neovascular Age-related Macular Degeneration: Two-Year Results - Martin, Daniel F; Maguire, Maureen G; Fine, Stuart L; Ying, Gui-Shuang; Jaffe, Glenn J; Grunwald, Juan E; Toth, Cynthia; Redford, Maryann; Ferris, 3rd, Frederick L (Ophthalmology (Rochester, Minn.), 2020)
To describe effects of ranibizumab and bevacizumab when administered monthly or as needed for 2 years and to describe the impact of switching to as-needed treatment after 1 year of monthly treatment. Multicenter, randomized clinical trial. Patients (n = 1107) who were followed up during year 2 among 1185 patients with neovascular age-related macular degeneration who were enrolled in the clinical trial. At enrollment, patients were assigned to 4 treatment groups defined by drug (ranibizumab or bevacizumab) and dosing regimen (monthly or as needed). At 1 year, patients initially assigned to monthly treatment were reassigned randomly to monthly or as-needed treatment, without changing the drug assignment. Mean change in visual acuity. Among patients following the same regimen for 2 years, mean gain in visual acuity was similar for both drugs (bevacizumab-ranibizumab difference, -1.4 letters; 95% confidence interval [CI], -3.7 to 0.8; P = 0.21). Mean gain was greater for monthly than for as-needed treatment (difference, -2.4 letters; 95% CI, -4.8 to -0.1; P = 0.046). The proportion without fluid ranged from 13.9% in the bevacizumab-as-needed group to 45.5% in the ranibizumab monthly group (drug, P = 0.0003; regimen, P < 0.0001). Switching from monthly to as-needed treatment resulted in greater mean decrease in vision during year 2 (-2.2 letters; P = 0.03) and a lower proportion without fluid (-19%; P < 0.0001). Rates of death and arteriothrombotic events were similar for both drugs (P > 0.60). The proportion of patients with 1 or more systemic serious adverse events was higher with bevacizumab than ranibizumab (39.9% vs. 31.7%; adjusted risk ratio, 1.30; 95% CI, 1.07-1.57; P = 0.009). Most of the excess events have not been associated previously with systemic therapy targeting vascular endothelial growth factor (VEGF). Ranibizumab and bevacizumab had similar effects on visual acuity over a 2-year period. Treatment as needed resulted in less gain in visual acuity, whether instituted at enrollment or after 1 year of monthly treatment. There were no differences between drugs in rates of death or arteriothrombotic events. The interpretation of the persistence of higher rates of serious adverse events with bevacizumab is uncertain because of the lack of specificity to conditions associated with inhibition of VEGF. Proprietary or commercial disclosure may be found after the references.